2020
DOI: 10.3390/s20195708
|View full text |Cite
|
Sign up to set email alerts
|

Condition-Based Maintenance with Reinforcement Learning for Dry Gas Pipeline Subject to Internal Corrosion

Abstract: Gas pipeline systems are one of the largest energy infrastructures in the world and are known to be very efficient and reliable. However, this does not mean they are prone to no risk. Corrosion is a significant problem in gas pipelines that imposes large risks such as ruptures and leakage to the environment and the pipeline system. Therefore, various maintenance actions are performed routinely to ensure the integrity of the pipelines. The costs of the corrosion-related maintenance actions are a significant por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…The optimal maintenance schedules are costeffective. When comparing the monthly average maintenance cost with 12 normal (periodic) maintenance costs retrieved from the literature (Mahmoodzadeh et al, 2020), the difference is noticeable as shown in Figure 58 and Table 14. As shown in Table 14, the optimization of the operating parameters aims at: (i) extending the lifetime of the pipeline, (ii) minimizing the maintenance cost, (iii) maximizing the economic profit, and (iv) minimizing the CO2 emission amount.…”
Section: Optimization Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The optimal maintenance schedules are costeffective. When comparing the monthly average maintenance cost with 12 normal (periodic) maintenance costs retrieved from the literature (Mahmoodzadeh et al, 2020), the difference is noticeable as shown in Figure 58 and Table 14. As shown in Table 14, the optimization of the operating parameters aims at: (i) extending the lifetime of the pipeline, (ii) minimizing the maintenance cost, (iii) maximizing the economic profit, and (iv) minimizing the CO2 emission amount.…”
Section: Optimization Resultsmentioning
confidence: 97%
“…Maintenance Activities and their related Cost and Downtime. The presented data are extracted from the literature (Mahmoodzadeh et al, 2020). The last step in the optimization model is to define the constraints.…”
Section: Objectives Of the Domso Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…While time-based PM schedules maintenance actions at fixed time-intervals, CBM reacts based on available information regarding the condition of a given component [9]. Due to its advantages many researchers have recently focused on CBM application to several fields [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%